Glatiramer acetate exposure in pregnancy: preliminary safety and birth outcomes - Salminen, Heidi J.; Leggett, Helen; Boggild, Mike (Journal of neurology, 2010)
With the increasing incidence of multiple sclerosis (MS) in women and the earlier use of disease modifying therapy (DMT), issues surrounding DMT and pregnancy are a regular subject of discussion with regards to optimal management. Current recommendations are to withdraw DMT prior to conception, leaving patients exposed to an uncertain period of untreated disease. The objective of this study is to report preliminary experience on glatiramer acetate (GA) exposure through conception, pregnancy and the post-partum period in a series of 13 patients with previously highly active relapsing-remitting MS. This is a prospective observational case series. Fourteen pregnancies of 13 women resulted in 13 live births (one twin pregnancy), nine exposed to GA throughout pregnancy. There were no birth defects and treatment was well tolerated. No relapses occurred during pregnancy in those continuing on treatment. In conclusion, our early experience suggests that when considering the risks and benefits of treatment withdrawal prior to pregnancy, it may be reasonable to continue GA in those patients with previously highly active disease. Consideration should also be given to the initiation of a birth register, similar to such initiatives in epilepsy, to generate more robust safety data in this controversial area.